Review or not review, there is the dilemma: brief reflections on the impugnability of dispute boards’ decisions on the arbitral route - Valverde, Gianpierre (2017)
The purpose of this article is to highlight the probable contingencies that could arise as a result of the review of the decisions of the Dispute Boards in the arbitration. To achieve this, the structure of the article is arranged in such a way as to facilitate the understanding of the conclusions.In that sense, first, the nature and function of the Dispute Boards is defined. The classes and advantages offered by these dispute resolution mechanisms are then indicated. Subsequently, the legal provision is analyzed in order to crumble its contents. The article ends with the analysis of the effects generated by reviewing the decisions of the Dispute Boards.